28. ANALYSIS OF FACTORS ASSOCIATED WITH THE INDICATION FOR INTEGRATING TRADITIONAL MEDICINE AND MODERN MEDICINE IN THE TREATMENT OF SPINAL OSTEOARTHRITIS AT THE UNIVERSITY MEDICAL CENTER HO CHI MINH CITY - BRANCH 3 AND HO CHI MINH CITY TRADITIONAL MEDICIN (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the factors associated with the integrated use of traditional medicine and modern medicine in the treatment of spinal osteoarthritis.Subjects and methods: A descriptive cross-sectional study was conducted on 1100 medical records of patients diagnosed with spinal osteoarthritis who received at least one form of traditional medicine or modern medicine at the University Medical Center Ho Chi Minh city - branch 3 and the Ho Chi Minh city Traditional Medicine Hospital from January 1, 2024 to December 31, 2024.Results: The median age of the study population was 50 years (range: 25-75 years), with females accounting for 66.7%. The prevalence of comorbidities was 67.5%, with musculoskeletal disorders being the most common (42.1%). Factors associated with the combined use of traditional medicine and modern medicine included the presence of comorbidities (OR = 1.47; 95% CI: 1.062-2.034; p = 0.02) and cardiovascular diseases (OR = 0.696; 95% CI: 0.488-0.993; p = 0.046).Conclusion: The integration of traditional medicine and modern medicine in the treatment of spinal osteoarthritis may be associated with the presence of comorbidities and cardiovascular diseases.
Keywords: Integration; spinal osteoarthritis; traditional medicine; modern medicine.